THE IMPACT OF GAZA FISHING HARBOUR ON THE MEDITERRANEAN COAST OF GAZA - Mazen Abualtayef; Said Ghabayen; Ahmed Abu Foul; Ahmed Seif; Masamitsu Kuroiwa; Yuhei Matsubara; Omar Matar (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The Mediterranean coast of Gaza strip, which is covered about 40 km in length, is rich by coastal resources. The development that occurred along the coastal lines has led to the host of problems such as increased erosion, siltation, loss of coastal resources and the destruction of the fragile marine habitats. In order to conserve the depleting coastal resources, the changes due to development and associated activities must be monitored. Studying the temporal pattern of shoreline change is considered one of the most effective means of monitoring the cumulative effects of different activities. An attempt was made to study the impact of Gaza harbour on shoreline displacement along 6 km. This paper was intended to detect changes of coastal area in Gaza city to provide future database in coastal management studies. The analysis was carried out using image processing technique (ERDAS) and Geographical Information System platform. The variation during 38 years in the shoreline along the Gaza coast was determined by analyzing MSS, TM and ETM Landsat images from 1972 to 2010. The analyses identified the erosion and accretion patterns along the coast. The shoreline was advanced south of the Gaza fishing harbor, where the wave-induced littoral transport was halted by southern breakwater and the annual beach growth rate was 15,900 m2. On the downdrift side of the harbor, the shoreline was retreating and beaches erode at an annual rate of -14,000 m2. This study was emphasized that the coastal band is considered as a critical area, it is therefore necessary to monitor coastal zone changes because of the importance of environmental parameter and human disturbance. In particular, the projections of future shoreline erosion and accretion rates are considered important for long-term planning and environmental assessment for a variety of projects, including the construction and tourism facilities.